PENINGKATAN PRODUKTIVITAS JASA CETAK PCB DENGAN MESIN ETCHING OTOMATIS DI KOTA PADANG - Andre, Hanalde; Albert, Muhammad Riski; Luthfi, Amirul; Pratama, Rizki Wahyu (Jurnal Hilirisasi IPTEKS, 2024)
Community activities aim to design and implement an automatic etching machine using a microcontroller and servo motor. The microcontroller acts as the control unit, regulating the movement of the servo motor to ensure the etching process runs with maximum efficiency. The method used in this activity is divided into several structured stages. The first stage is design, where the device is designed using a microcontroller to control the servo motor responsible for moving the PCB undergoing the etching process. The second stage is implementation, where the components to be used include the microcontroller, servo motor, LCD, buttons, and etching container. The final stage is evaluation, where the created device is assessed based on the suitability of the motor movements produced according to the main objective, which is to produce tracks as desired by the operator. The results of implementing this automatic etching machine activity are expected to provide several key benefits. Firstly, the machine can reduce the time required to complete the PCB etching process, thereby increasing productivity in PCB printing services. Additionally, by reducing human involvement in the monotonous physical process, this machine helps avoid human errors and thus can improve the quality of the products produced. In conclusion, it is hoped that the PCB printing service industry can take a step forward in adopting automation technology that can enhance production efficiency and product quality.